2012
DOI: 10.1029/2012jg002016
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale channels on ectomycorrhizal‐colonized chlorite: Evidence for plant‐driven fungal dissolution

Abstract: [1] The roots of many trees in temperate and boreal forests are sheathed with ectomycorrhizal fungi (EMF) that extend into the soil, forming intimate contact with soil minerals, from which they absorb nutrient elements required by the plants and, in return, are supported by the organic carbon photosynthesized by the trees. While EMF are strongly implicated in mineral weathering, their effects on mineral surfaces at the nanoscale are less documented. In the present study, we investigated the effects of symbioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Trenching and pitting of minerals by fungal hyphae indicates dissolution and mass loss from the mineral, as shown for biotite and chlorite weathered by EM fungi in axenic culture with host tree seedlings (Bonneville et al, 2009;Gazzè et al, 2012;Saccone et al, 2011) and in liquid culture (Balogh-Brunstad et al, 2008). Collectively, the evidence indicates that fungal attack of the mineral occurs on exposed outer surfaces and also between the sheets of muscovite.…”
Section: Mineral Surface Alterationmentioning
confidence: 74%
See 1 more Smart Citation
“…Trenching and pitting of minerals by fungal hyphae indicates dissolution and mass loss from the mineral, as shown for biotite and chlorite weathered by EM fungi in axenic culture with host tree seedlings (Bonneville et al, 2009;Gazzè et al, 2012;Saccone et al, 2011) and in liquid culture (Balogh-Brunstad et al, 2008). Collectively, the evidence indicates that fungal attack of the mineral occurs on exposed outer surfaces and also between the sheets of muscovite.…”
Section: Mineral Surface Alterationmentioning
confidence: 74%
“…Extensive networks of root-associating hyphae extend into the soil to enhance essential nutrient element mass transfers from solid and liquid phases to plants by enhancing the intimacy of mineral contact and absorptive surface areas relative to roots (Smith and Read, 2008;Taylor et al, 2009). The mechanistic basis underpinning mycorrhizal hyphal-mineral interaction is being resolved at the nanometre scale, with recent observations demonstrating structural alterations and mineral surface trenching through the effects of organic ligand exudation, such as siderophores and low-molecular-weight organic compounds, proton extrusion and cation uptake (Bonneville et al, 2009;Gazzè et al, 2012;Saccone et al, 2011). Such effects are most strongly expressed in EM fungi (Lambers et al, 2009;Taylor et al, 2009;Landeweert et al, 2001), which molecular clocks indicate originated 220-135 million years (Ma) ago (Smith and Read, 2008;Taylor et al, 2009 and references therein), more than 200 Ma after ancestral AM fungi (Brundrett, 2002;Taylor et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In natural settings, however, biotite is a prime source of nutrients (K in particular) and thus biotic processes may play an important role in element release. Several recent studies have demonstrated that microorganisms influence phyllosilicate weathering through a combination of physical and chemical alteration, or 'bio-fracking' (Balogh-Brunstad et al, 2008;Bonneville et al, 2009Bonneville et al, , 2011Hopf et al, 2009;Balland et al, 2010;Saccone et al, 2012;Gazzè et al, 2012Gazzè et al, , 2013. One bio-mediated mechanism is changing the chemical composition of the local environment, i.e., localised acidification (Balogh-Brunstad et al, 2008;Bonneville et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies emphasized the potential importance of localized microbial effects on mineral dissolution caused by surface attachment (Jongmans et al, 1997;Barker et al, 1997;Banfield et al, 1999;Rosling et al, 2004b), and the exchange of protons for base cations at the attachment locus (Jenny, 1980;Fomina et al, 2006;Wallander, 2006;Balogh-Brunstad et al, 2008b). According to Gazzè et al (2012) the weathering of minerals by fungi may also have a mechanical nature since the internal pressure in hyphae can reach values between 0.4 and MPa, and can produce structural alterations of phyllosilicates (Bonneville et al, 2009), possibly by causing strain in the mineral during hyphal growth. The above mechanisms of fungal dissolution of minerals have been summarized by Fomina et al (2007), who categorize them as biomechanical and biochemical, the latter produced by acidolysis and complexolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal capacity to dissolve minerals has been mainly investigated in order to establish the overall ability of fungi to extract nutrients from the minerals (Barker et al, 1997;Hopf et al, 2009;Paris et al, 1995;Yuan et al, 2004). The more restricted attention to dissolution mechanisms has resulted in a limited documentation of microscale tracks on mineral surfaces (Bonneville et al, 2009;Gazzè et al, 2012). Balogh-Brunstad et al (2008b) observed that fungal action in liquid culture caused K, Mg and Fe removal from biotite and incorporation into fungal biomass without production of SEM-detectable marks on the mineral surface.…”
Section: Introductionmentioning
confidence: 99%